Evidence, sex and state paternalism. Intersecting global connections in the introduction of HPV vaccines in Colombia (2017)
HPV (human papillomavirus) vaccines provide an opportunity to trace local connections that configure the global circulation of drugs (see Lindén (Chap.6, this volume); Lindén and Busse (Chap.9, this volume); Hanbury (Chap.8, this volume); Johnson et al. 2016). The multiple and almost simultaneous reception of HPV vaccines in different countries shows the local adaptation, translation and enactment of some “global” narratives, policies and market strategies around drugs. In the case of HPV vaccines, narratives around girlhood, women’s empowerment, motherhood and parental care have had a global reach through vaccination campaigns, advertisements and public health discourses. The reactions of parents, media and government to these discourses have varied from country to country, some showing similarity, others marked differences. For instance, the involvement of politicians with the HPV vaccination has varied from explicit political debate (e.g., the United States), to political consensus (Mexico, Brazil and Colombia), to silence and no explicit involvement (e.g., the UK and Sweden).